EFEKTIVITAS KEPEMIMPINAN DI FKIP UPP - ., Hardianto (Universitas Pasir Pengaraian, 2016)
The puposes of this study was to provide an overview of the effectiveness of leadership in FKIP UPP. The effectiveness of leadership will be seen from the style in giving orders, force in giving the award, the style in taking decisions and style ofdelegating authority.This research was quantitative descriptive. The population of this study wasFKIP UPP Lecturers. Questionnaires were distributed to all lecturers and returned about 32 pieces. The sample was taken by total sampling technique. The instrument used was a questionnaire with Likert scale model. Data was analyzed by using descriptive analysis.The result of the research shows that generally, the leadership style in FKIP UPP was a democratic leadership style (48.89%). The styleof leadership in providing the order was the democratic style (57.03%). Leadership style in giving the award was laissez faire style (51.04%). Style of leadership in taking decision was the democratic style (46.87%). Leadership style in delegating authority was democratic style (43.75%).